350. SALVAGE RADIATION THERAPY FOR OLIGO-RECURRENCES AFTER RADICAL TREATMENT OF ESOPHAGEAL CANCER. (24th September 2022) - Mummudi, Naveen; Srinivasan, Shashank; Jiwnani, Sabita; Tibdewal, Anil; Karimundackal, George; Pramesh, CS; Agarwal, Jai Prakash
Abstract: Loco-regional recurrences following surgery or radical radiation therapy for esophageal cancers represent a significant clinical problem. We performed a retrospective study to assess the safety and efficacy of salvage radiation for oligo-recurrence after primary curative therapy for esophageal cancer. Esophageal cancer patients treated with salvage radiotherapy between January 2011 and March 2020 at our institution were screened. Patients were included if they had undergone prior treatment for esophageal carcinoma with curative intent using either surgery or radiotherapy and had developed local/locoregional/isolated distant recurrences. Recurrences were diagnosed based on CT scan or/and FDG PET-CT scan. Treatment plan was discussed in a multi-disciplinary tumour board and patients were followed up as per institution policy. Survival rates were estimated using the Kaplan–Meier method and data was analyzed using IBM SPSS Statistics for Windows (Version 26.0. Armonk, NY: IBM Corp.) Oligo-recurrence was diagnosed in 33 patients; thirty patients had loco-regional-recurrence (LRR), 3 had distant metastasis); 28 patients underwent surgery as initial treatment; 5 received definitive RT. Recurrence was detected at a median of 21 months. Of the 30 patients with LRR, 25 patients received chemo-radiation and 5 received RT alone. At a median follow-up of 18 months, 20 patients were alive and 61% had controlled disease. Overall survival at 1- & 2- year were 83% and 65% respectively. Concurrent chemotherapy administration and RT dose of >56Gy were independent predictors for OS. No grade 3/4 acute or chronic toxicity were observed. Salvage RT with or without concomitant chemotherapy for loco-regional recurrences after surgery for esophageal cancer is safe and effective. Advanced, modern RT techniques may reduce treatment related morbidity and improve outcomes.